Esophageal carcinosarcoma comprised of minimally invasive squamous cell carcinoma and undifferentiated pleomorphic sarcoma: A collision cancer?. Issue 8 (22nd June 2018) - Miyauchi, Jun; Ogura, Masaharu; Sato, Michio; Matsui, Junichi
Abstract : Esophageal carcinosarcoma is a rare neoplasm with components of squamous cell carcinoma and sarcomatous spindle cell stroma. The latter may show overt mesenchymal differentiation but is thought to be derived from carcinoma cells in most cases. Here, we report a case of esophageal carcinosarcoma that appeared to be comprised of different origins of epithelial and mesenchymal tumor cells. The sarcomatous component formed an intralumial pedunculated large mass lesion that consisted of pleomorphic atypical histiocyte‐like cells. The squamous epithelium exhibited features of mostly dysplasia with minor foci of microinvasive squamous cell carcinoma. The invasive carcinoma was apart from the sarcoma, and no transitions were observed between the epithelial and sarcomatous cells. Immunohistochemistry showed that the sarcoma cells did not express any lineage‐specific markers, including those for epithelial cells and histiocytes, which lead to the diagnosis of undifferentiated pleomorphic sarcoma. Although cyclin D1 was overexpressed in the carcinoma cells, it was nearly negative in the sarcoma cells. These findings indicate that the tumor may be a collision carcinosarcoma. It is highly likely that the patient's history of heavy smoking and alcohol consumption were relevant to the pathogenesis, at least for the epithelial component, of the tumor.